THE 3 MOST COMMON MISTAKES IN IELTS/CEFR PREPARATION: (NOT ADAPTING TO THE EXAM FORMAT, POOR TIME MANAGEMENT, AND INSUFFICIENT - Ravshanova Marjona Jumaniyoz qizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article analyzes the three most widespread mistakes that hinder candidates preparing for the IELTS  and CEFR exams from achieving high scores. The main  goal  is  to  demonstrate  that  strategic  preparation  is  equally  as  important  as language proficiency itself.The key mistakes examined are:Not Adapting to the Exam Format: Candidates' lack of understanding regarding the specific question types and scoring criteria in each section.Poor Time Management: The lack of skills necessary to  efficiently  complete  the  test  within  the  strict  time  limits.Insufficient  Practice: Neglecting regular and focused practice, especially in the active skills (Writing and Speaking).The  article  offers  practical  solutions  and  strategies  to  overcome  each mistake, emphasizing the necessity of a strategic approach to the preparation process. Adherence to these recommendations will help candidates maximize the demonstration of their knowledge under exam conditions.